Mitochondrial DNA insertions into nuclear genome (numts) in Vietnam sheep: Implications and caveats for the utility of the mitochondrial DNA markers in genetic diversity studies in sheep - Nguyen, Ngoc Luong; Nguyen, Nhu Cuong; Ha Huynh, Thi Thu (Vietnam Journal of Biotechnology, 2023)
Nuclear insertions of mitochondrial DNA sequences (numts) can introduce errors in population genetic studies using mitochondrial DNA markers (mtDNA markers). Despite their prevalence in mammalian genomes and the potential risk of contamination with mtDNA markers, adequate precautions are often overlooked. When investigating the genetic diversity of Vietnam sheep, we found numt contamination in D-loop amplification. Consequentially, to continue, we conducted a comprehensive in silico survey of numts using the reference genomes from the NCBI database. We identified four so-called “mega-numts” that are not only highly similar in sequence to the mitogenome but also span a large part of it, thus posing a serious problem for amplifying authentic mtDNA markers. We demonstrated the existence of two numts in three randomly selected Vietnam sheep individuals. Based on the assumed mutation rate of the D-loop region, we proposed a sequence identity threshold to help distinguish authentic D-loop sequences from their corresponding numts when studying contemporary sheep populations. We hope this study can serve as a guideline for future research into Vietnam sheep using mtDNA markers.